Analisis Butir Soal Semester Ganjil Mata Pelajaran Matematika pada Sekolah Menengah Pertama - Anetha L. F. Tilaar; Hasriyanti Hasriyanti (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2019)
Abstract The results of the initial interview, it was revealed that every time the final school exam was conducted, the questions tested had not been analyzed as a whole, so the quality of the questions was unknown. Therefore this study aims to analyze the odd semester final exam items in mathematics in SMP Negeri 4 Pineleng in the 2018/2019 school year in terms of reliability, validity, distinguishing features, level of difficulty and effectiveness of deceivers (specifically multiple choice questions). This type of research is a descriptive analysis with a quantitative approach. The number of subjects in this study were 97 students consisting of all VIII grade students of SMP Negeri 4 Pineleng in the 2018/2019 school year. The data collection technique used is documentation. The data is processed manually with the help of the excel program and uses the help of the Anatest Version 4 program specifically to analyze effectiveness. From the results of the analysis it can be concluded that the final semester exams for the mathematics students of SMP Negeri 4 Pineleng in the 2018/2019 school year: (1) Types of multiple choice questions, 5 questions or 16.67% have very good quality so they can be stored in the question bank for reuse , 15 questions or 50.00% still need to be revised and 10 questions or 33.33% have very poor quality so that they cannot be stored in the question bank. (2) The types of description questions, 2 questions or 40.00% have good quality, 2 questions or 40.00% need to be revised, 1 problem or 20.00% have bad quality.AbstrakHasil wanwancara awal, terungkap bahwa setiap pelaksanaan ujian akhir sekolah, soal yang diujikan belum dianalisis secara keseluruhan, sehingga kualitas soal tersebut tidak diketahui. Oleh karena itu penelitian ini bertujuan untuk menganalisis butir soal ujian akhir semester ganjil mata pelajaran matematika SMP Negeri 4 Pineleng tahun ajaran 2018/2019 ditinjau dari reliabilitas, validitas, daya pembeda soal, tingkat kesukaran dan efektifitas pengecoh (khusus soal pilihan ganda). Jenis penelitian ini adalah analisis deskriptif dengan pendekatan kuantitatif. Jumlah subjek dalam penelitian ini adalah 97 siswa terdiri dari seluruh siswa kelas VIII SMP Negeri 4 Pineleng tahun ajaran 2018/2019. Teknik pengumpulan data yang digunakan adalah dokumentasi. Data diolah secara manual dengan bantuan program excel dan menggunakan bantuan program Anatest Versi 4 khusus untuk menganalisis efektifitas. Dari hasil analisis dapat disimpulkan bahwa ujian akhir semester ganjil mata pelajarn matematika SMP Negeri 4 Pineleng tahun ajaran 2018/2019 : (1) Jenis soal pilihan ganda, 5 soal atau 16.67% memiliki kualitas sangat baik sehingga dapta disimpan di bank soal untuk dapat digunakan kembali, 15 soal atau 50.00% masih perlu direvisi dan 10 soal atau 33.33% memiliki kualitas sangat tidak baik sehingga tidak dapat disimpan di bank soal. (2) Jenis soal uraian, 2 soal atau 40.00% memiliki kualitas baik, 2 soal atau 40.00% perlu direvisi, 1 soal atau 20,00% meiliki kualitas tidak baik.